Angular Dependence of the Magnetic Properties of Cylindrical Diameter Modulated Ni80fe20 Nanowires - Escrig-Murua, J; Espejo-Pina, A; Tejo-Lazo, F; Vidal-Silva, N (American Institute of Physics, 2014)
We have investigated numerically the angular dependence of the coercivity and remanence of cylindrical diameter modulated Ni80Fe20 nanowires. We observed that the system always starts reversing its magnetization through the thickest segment by means of a quite complex reversal process, considering the propagation of two vortex domain walls. Furthermore, we observed a transition from vortex domain walls to coherent-mode rotation for the thinnest segment as a function of the angle in which the external magnetic field is applied. In addition, we obtained a non-monotonic behavior for the coercivity and saturation field as a function of the angle at which the external magnetic field is applied. Finally, diameter modulation is an attractive way to handle over the motion of magnetic domain walls, a phenomenon proposed as a future data storage platform. © 2014 AIP Publishing LLC.